Protein Kinase A and Anxiety-Related Behaviors: A Mini-Review - Keil, Margaret F.; Briassoulis, George; Stratakis, Constantine A.; Wu, T. John (Frontiers in Endocrinology, 2016)
This review focuses on the anxiety related to cyclic AMP (cAMP)/protein kinase A (PKA) signaling pathway that regulates stress responses. PKA regulates an array of diverse signals that interact with various neurotransmitter systems associated with alertness, mood, and acute and social anxiety-like states. Recent mouse studies support the involvement of the PKA pathway in common neuropsychiatric disorders characterized by heightened activation of the amygdala. The amygdala is critical for adaptive responses leading to fear learning and aberrant fear memory and its heightened activation is widely thought to underpin a variety of anxiety disorders. Stress-induced plasticity within the amygdala is involved in the transition from normal vigilance responses to emotional reactivity, fear over- generalization, and deficits in fear inhibition resulting in pathological anxiety and conditions, such as panic and depression. Human studies of PKA signaling defects also report an increased incidence of psychiatric disorders, including anxiety, depression, bipolar disorder, learning disorders, and attention deficit hyperactivity disorder. We speculate that the PKA system is uniquely suited for selective, molecularly targeted intervention that may be proven effective in anxiolytic therapies.